In vitro propagation of Eranthis longistipitata and its phytocomponent analysis - ZHANAR E. AIMENOVA; ALIMZHAN D. MATCHANOV; SAYYORA SH. ABDIRAHIMOVA; RAHMAT S. ESANOV; AIDAR A. SUMBEMBAYEV; SHYNGISKAN E. DUISSEBAYEV (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Aimenova ZE, Matchanov AD, Abdirahimova SS, Esanov RS, Sumbembayev AA, Duissebayev SE. 2024. In vitro propagation of Eranthis longistipitata and its phytocomponent analysis. Biodiversitas 25: 4171-4178. Eranthis longistipitata is an endemic plant of Central Asia. The available literature indicates the great potential of Eranthis plants for use in various branches of pharmacology and medicine. The medical use of this plant is limited by its short flowering period and narrow range of growth. In this paper, we present the results of a study on the micropropagation of this species. As a result of the selection of the modification medium supplemented with benzylaminopurine, kinetin and Indolyl-3-butyric acid we obtained calluses from E. longistipitata. Since some of the most valuable biologically active substances in E. longistipitata are flavonoids such as rutin, isorhamnetin, and hyperoside, we investigated their presence in the calluses via High-performance liquid chromatography. The elemental composition was established for the first time via the Inductively Coupled Plasma (ICP) method, and the antioxidant activity was investigated via the Ferric Reducing Antioxidant Power (FRAP) assay. Toxicity was assessed via the brine shrimp assay. Extracts of E. longistipitata leaves, including those obtained with chloroform, ethyl acetate, and ethanol, were prepared to investigate their antioxidant and cytotoxic properties. The elemental composition analysis of callus tissue revealed the presence of potassium at a concentration of 19.516 mg/10 g and sulfur at 17.802 mg/10 g, with no trace of heavy metal ions or toxic elements detected. The study of the antioxidant activities of the leaf extracts revealed that the ethanol extract presented the highest capacity at a concentration of 1 mg/mL. The toxicity analysis of the leaf extracts revealed no toxicity toward the Artemia salina larvae used in the experiment.